Water and complex problemsheds in Karamoja, Uganda - Nicol, Alan; Debevec, Liza; Ayaru, Samuel Okene (Routledge, 2022)
A complex political economy revolves around shared land and water use between Kenyan Turkana and Ugandan Karamojong pastoralists. In response to growing pressure on resources, donors and the Ugandan government are investing in new surface water sources. However, power and political economy issues embedded within societal relationships are rarely factored into water infrastructure development. Drawing on Tony Allan's teaching, we examine studies of two dams recently constructed in Karamoja and argue that a wider view encompassing power and politics within the Karamoja-Turkana Complex would help ensure more sustainable and effective future water supply development. Allan's idea that catchments are part of much wider social, political economic and integrated livelihood systems, or problemsheds, is a key concept. Here we argue that adopting this concept in a complex of pastoral systems can improve future water resources planning and intervention in Karamoja, Uganda and similar contexts.
Keywords: problemshed, pastoralism, water security, Karamoja